Cyclic tensile strain-induced yes-associated protein activity modulates the response of human periodontal ligament mesenchymal stromal cells to tumor necrosis factor-α. (November 2022) - Zhao, Zhongqi; Behm, Christian; Tian, Zhiwei; Rausch, Marco Aoqi; Rausch-Fan, Xiaohui; Andrukhov, Oleh
Abstract: Objectives: This study aimed to evaluate the role of yes-associated protein (YAP) in the inflammatory processes induced in human periodontal ligament-derived mesenchymal stromal cells (hPDL-MSCs) by cyclic tensile strain (CTS). Design: hPDL-MSCs from five periodontally healthy individuals were stimulated with 12% CTS and/or TNF-α for 24 h. YAP activity was determined by analyzing the YAP nuclear localization and the target genes expression, using immunofluorescence and qPCR, respectively. Verteporfin was used to inhibit the activation of YAP. The gene expression of interleukin (IL)-6, IL-8, vascular cell adhesion molecule (VCAM)-1, and intercellular adhesion molecule (ICAM)-1 was analyzed by qPCR. Results: In the absence of TNF-α, application of CTS resulted in the nuclear YAP translocation and upregulation of YAP target genes. Verteporfin inhibited the activation of YAP pathway and upregulated the basal expression of IL-6 and IL-8. TNF-α induced the activation of YAP pathway, which was inhibited by verteporfin. However, application of CTS under these conditions diminished TNF-α-induced YAP activation. TNF-α-induced expression of IL-6, VCAM-1, and ICAM-1 was inhibited after the application of CTS. Inhibition of YAP activation by verteporfin diminished TNF-α-induced gene expression of IL-6, VCAM-1, and ICAM-1, and under these conditions no inhibitory effect of CTS on these parameters was observed. Conclusions: YAP is at least partially involved in the CTS-activated mechanotransduction pathway. The effects of CTS and YAP on the inflammatory responses depend on the inflammatory environment. A better understanding of the inflammatory modulation by mechanical stress may help improve the orthodontic strategies, especially in the patient with periodontitis. Highlights: Yes-associated protein (YAP) mediates the effects of cyclic tensile strain. YAP can be either pro- or anti-inflammatory depending on the environment. YAP is involved in the interaction between mechanotransduction and inflammation.